Halakah and Mark 7.3: ‘with the hand in the shape of a fist’ - Crossley, James G. (New Testament studies, 2012)
This article argues that πυγμῇ in Mark 7.3 is not as mysterious as much of the history of scholarship has suggested. It seems clear that πυγμῇ reflects a known purity practice in early Jewish law concerned with using the minimal amount of water required for hand-washing. The hand would be sufficiently relaxed in order that an economic use of water poured on it could seep through the fingers to cover enough of the hand required for proper purification. The literal translation ‘fist’, at least with the sense ‘in the form of a fist’, is the most obvious translation of πυγμῇ when placed in the context of hand-washing law.